2017
DOI: 10.1128/jvi.01859-16
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Human Astrovirus Capsid-Antibody Complex and Mechanistic Insights into Virus Neutralization

Abstract: Human astroviruses (HAstVs) are a leading cause of viral diarrhea in young children, the immunocompromised, and the elderly. There are no vaccines or antiviral therapies against HAstV disease. Several lines of evidence point to the presence of protective antibodies in healthy adults as a mechanism governing protection against reinfection by HAstV. However, development of anti-HAstV therapies is hampered by the gap in knowledge of protective antibody epitopes on the HAstV capsid surface. Here, we report the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…To identify the neutralization epitopes on the HAstV capsid, we first evaluated the capacity of the core and spike domains to induce total (determined by enzyme-linked immunosorbent assay [ELISA]) and neutralizing antibodies. These two structural domains of the virus can be produced in Escherichia coli in a soluble and correctly folded form (10)(11)(12)(13)(14). Rabbits and mice were immunized with either the purified, recombinant core or the spike domain of HAstV-1 (core1 or spike1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify the neutralization epitopes on the HAstV capsid, we first evaluated the capacity of the core and spike domains to induce total (determined by enzyme-linked immunosorbent assay [ELISA]) and neutralizing antibodies. These two structural domains of the virus can be produced in Escherichia coli in a soluble and correctly folded form (10)(11)(12)(13)(14). Rabbits and mice were immunized with either the purified, recombinant core or the spike domain of HAstV-1 (core1 or spike1).…”
Section: Resultsmentioning
confidence: 99%
“…Cryo-electron microscopy of mature HAstV virions reveals particles of 44 nm comprised of a T ϭ 3 icosahedral shell and 30 globular spikes (9). The crystal structures of both VP34 (10,11) and VP25 (11)(12)(13)(14) have been recently determined; VP34 folds into a domain that constitutes the shell of the virus capsid (core domain), while VP27/VP25 form dimeric capsid spikes (spike domain). VP34 is derived from the highly conserved N-terminal region of VP70, while VP27/VP25, which differ only at their amino termini, are derived from the hypervariable region of VP70 (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both the ORF1a and ORF1b encode the nonstructural proteins (NSPs), containing enzymes and participating in viral replication, whereas the ORF2 encodes the viral capsid polyprotein [20,21]. ORF2, containing antigenic determinant, can induce the production of neutralizing antibody interacting with the host [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Human astroviruses are recognized as an endemic cause of acute gastroenteritis globally [10]. Serological studies have shown that up to 90% of individuals in certain populations have antibodies against HAstVs [11,12]. These viruses are transmitted by the fecal-oral route, from person to person and from animals to humans [10].…”
Section: Introductionmentioning
confidence: 99%